Exploring the Stimulus From Social Media, Entrepreneurial Personality Towards Entrepreneurial Interest in the University - Arni, Yusni (Jurnal Entrepreneur dan Entrepreneurship, 2023)
This research aims to explore the stimulus of social media, entrepreneurial personality towards entrepreneurial interest. Data from 360 respondents was collected online from public and private universities in Indonesia. The statistics were examined using SEM-PLS 3.2.7. Seven research hypotheses were investigated in this study and also the stimulus for receiving benefits from social media is a significant result. The discovery of this inquiry too subscribe to the conceptual model of entrepreneurial interest which emphasizes the acceptance of technology to the wider entrepreneurial personality to increase entrepreneurial interest under future uncertainty. It is recommended to increase the use of e-learning applications and entrepreneurship training in order to motivate entrepreneurial interest.